The influence of online brand community characteristics in Facebook on brand loyalty / Nursaida Alina Mohammad Sairi - Mohammad Sairi, Nursaida Alina (Faculty of Business and Management, 2018)
Extreme competition in the business environment forces firms to look for the best tactic to attract and create brand loyalty. Online brand community is a strategy used by many firms to maintain brand loyalty. Good implementation of online brand community characteristics strategies will result in quality built between host of the community members, participants as well as customers and firms. The main study of this research is to investigate the impact of online brand community characteristics in Facebook on brand loyalty. Brand loyalty being a dependent variables in this research and measured by four independent variables which is system quality, rewards, information quality and virtual interactivity. A review of literature was conducted to find out the brand loyalty on online brand community in Facebook. The literature review confirms this relationship. This research is based on 132 respondents which collect in Jalan Hang Tuah, Bandaraya Melaka. Sampling method used in this study is convenience sampling. The data was analysed using correlation coefficient and regression by using SPSS software. The findings claims that are positive relationship between these online brand community characteristics and brand loyalty. Thus, the findings shows that only virtual interactivity has the strongest impact on brand loyalty.